Old-Age Security Protection for Government Employees with Work Agreements Is Reviewed According to The National Social Security System - Tanti Kirana Utami (Sociological Jurisprudence Journal, 2022)
Government Employees with Work Agreements are required to provide public services, improve professionalism and competence, and performance in government agencies. For that, the government must provide protection. Based on the preceding, the authors will conduct research that includes the safety of government employees with work agreements and old-age insurance arrangements for government employees with work agreements. The research method used is a normative juridical method with descriptive-analytical research specifications and analyzed using qualitative juridical methods. Everyone has the right to social security to fulfill the basic needs of a decent life and increase his dignity towards the realization of a prosperous, just. For those Government Employees with a Work Agreement, Prosperous Indonesian society is given protection by the government in old-age insurance, health insurance, accident insurance, employment, death insurance, and legal aid. There needs to be an arrangement to protect old-age security as long as the contract is regulated based on a national social security system that is in line with the Employment Social Security Organizing Agency to provide welfare both during the employment relationship and after the termination of the employment relationship.